Air travel attitude functions. Issue 2 (1st February 2020) - Cocolas, Nicole; Walters, Gabrielle; Ruhanen, Lisa; Higham, James
Abstract: Forecast growth in global demand for air travel is incompatible with emissions reduction targets. Scholarly attention is urgently needed to address attitude and behaviour change that supports sector-wide emissions reduction. Informed by the longstanding field of consumer psychology, the innovative approach adopted in this paper is to critically address air travel behaviour change through the application of attitude function theory. An analysis of the literature reveals that current attitudes reflect industry myths, and are further hampered by travellers' knowledge gaps regarding the relationship between aviation and climate change. Five attitude functions are analysed in the context of attitudes to air travel; knowledge, utilitarian, value-expressive, ego-defensive and social adjustive functions. A conceptual framework is presented that integrates attitude structure, attitude function and the elaboration likelihood model of persuasion as an innovative approach to address discretionary air travel and behaviour change at the level of the individual consumer. Utilizing this framework, future research can help develop a critical understanding of the antecedents that shape attitudes. Researchers will be better positioned to create persuasive messages aimed at changing attitudes towards air travel, as arguably the key step towards the illusive goal of significant behaviour change and a shift towards more sustainable tourist mobilities.